KEPEMIMPINAN DI ERA DISRUPSI: ANALISIS BIBLIOMETRIK DAN EVOLUSI TEMATIK PENELITIAN KEPEMIMPINAN DALAM MANAJEMEN SUMBER DAYA MANUSIA - Shandi, Arie; Maryadi; Muhammad Idris (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the evolution of leadership in the era of disruption through a bibliometric approach to 164 articles indexed in Scopus between 2003 and 2025. Articles from discontinued journals were excluded to maintain the relevance and quality of the data. The analysis results show an annual growth rate of 14.52% in publications written by 570 authors worldwide, reflecting the increasing attention to leadership studies in the face of global complexity and uncertainty. The results indicate that the USA is the most cited country and Malik P is the most relevant author. The findings show that digital transformation is the most relevant topic today, in line with the rapid development of technology and digital acceleration post-COVID-19 pandemic. Additionally, health issues have emerged as an important focus, indicating a shift in the role of leaders to not only focus on technological innovation but also on employee well-being. The co-occurrence network analysis revealed three main clusters: red (leadership and human resource management in the context of digitalization), green (leadership in the health and education sectors), and blue (macro issues such as sustainable development and global labor).